2012
DOI: 10.1111/j.1745-4549.2012.00745.x
|View full text |Cite
|
Sign up to set email alerts
|

ESTIMATION OF THE THERMOCHEMICAL NONISOTHERMAL INACTIVATION BEHAVIOR OF BACILLUS COAGULANS SPORES IN NUTRIENT BROTH WITH OREGANO ESSENTIAL OIL

Abstract: The aim of this work was to validate the prediction of the nonisothermal thermochemical inactivation of Bacillus coagulans spores in nutrient broth, adjusted to 4 °Brix and pH 4.2, with 400 ppm of oregano essential oil (EO), using the Weibull dynamic model proposed by Peleg. First, the spores were heat treated at four constant temperatures. Afterwards, empirical secondary models were employed to describe the influence of temperature on the primary parameters. Finally, primary and secondary models were used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…These authors verified that there was general agreement between the predicted and observed survival curves. Haberbeck and others () also tested the applicability of the methodology proposed by Peleg and Penchina () comparing the predicted curves with experimental ones obtained with B. coagulans spore inactivation in nutrient broth, added with 400 ppm of oregano essential oil and heat treated under 2 nonisothermal temperature profiles, ranging from 90 to 95 °C. In contrast to the present work, these authors observed faster experimental inactivation than the model prediction.…”
Section: Discussionmentioning
confidence: 99%
“…These authors verified that there was general agreement between the predicted and observed survival curves. Haberbeck and others () also tested the applicability of the methodology proposed by Peleg and Penchina () comparing the predicted curves with experimental ones obtained with B. coagulans spore inactivation in nutrient broth, added with 400 ppm of oregano essential oil and heat treated under 2 nonisothermal temperature profiles, ranging from 90 to 95 °C. In contrast to the present work, these authors observed faster experimental inactivation than the model prediction.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the microbial responses of three microorganisms with different inactivation kinetics have been extracted from the scientific literature: Escherichia coli in peptone water (Garre, Clemente-Carazo, Fernández, Lindqvist, &Egea, 2018), Salmonella enteric subsp. enterica serovar Senftenbergin peptone water (Huertas, Ros-Chumillas, Esteban, Esnoz, &Palop, 2015) and Bacillus coagulansin nutrient broth supplemented with oregano oil (Haberbeck, Dannenhauer, Salomão, & De Aragão, 2013).These microorganisms present survivor curves with different shapes, that include upward and downward concavity, as well as linear responses. Furthermore, their D (and 𝛿) values varies by at least one order of magnitude.…”
Section: Mathematical Modelling Of Microbial Inactivationmentioning
confidence: 99%